Impact of inner reservoir faults on migration and storage of injected CO2. (May 2018) - Yang, Zhijie; Xu, Tianfu; Wang, Fugang; Yang, Yanlin; Li, Xufeng; Zhao, Ningning
Highlights: A three-dimensional numerical model of a faulted reservoir system is presented, based on the seismic exploration data. The effects of inner reservoir faults on CO2 migration and storage capacity of the injected CO2 are investigated. More attentions should be paid to the impact of faults on the migration of CO2 in the caprock. Abstract: CO2 geological storage (CGS) is an effective way to mitigate greenhouse gas emissions, and geological security is one of the most important issues in CGS. The faults distributed in geological formations make multi-layered reservoirs interconnected systems. A three-dimensional (3D) numerical model was established to evaluate the effects of inner reservoir faults on the CO2 migration and storage capacity of an actual CGS demonstration project in the Ordos Basin of China. The results show that the faults in the layered reservoir system could significantly affect the migration of injected CO2 . The cross-layer faults at the bottom of the faulted reservoir could act as preferential passages between the upper and lower geological formations, causing the CO2 in the reservoir formation to move upward to adjacent layers rather than to lateral migration. CO2 migration along the inner-layer faults widely occurred at the top of the reservoir formation, decreasing the pressure accumulation and CO2 saturation around the injection well. Based on the simulation, CO2 will have migrated into the Heshanggou Formation after 300 years, and most of the CO2 will be trapped in the bottom sub-layers, with no CO2 intruding into the upper caprock. The spatial and temporal evolution of the injected CO2 was well presented for the faulted reservoir system, suggesting that the faults inside the multi-layered reservoir are beneficial to CGS.